New Frontiers in Angiogenesis - Forough, Reza (Springer Netherlands : Imprint: Springer, 2006)
New Frontiers in Angiogenesis starts with a comprehensive overview of the field and continues with topics that have been minimally explored. The topics deal with dynamics of vasculogenesis using imaging techniques, bone marrow-derived endothelial cell precursors as potential therapeutic tools, regulation of post-angiogenic vessel regression, vascular mimicry, design and construction of artificial vessels, bioengineering of angiogenesis, and lymphangiogenesis recapitulating angiogenesis in health and disease states. Each chapter is written by leading experts of the subjects. It is hoped that this volume will challenge all of us interested in the field of angiogenesis and cardiovascular biology, in particular those in academia and industries, to think "outside the box" and explore angiogenesis from a fresh angle. It is hoped that New Frontiers in Angiogenesis is thought provoking and serve as a road map for discovering new findings to help betterments of human health.